RANCANG BANGUN SISTEM MONITORING KUALITAS UDARA (PM2.5 DAN PM10) DI TAMAN SINGHA MERJOSARI BERBASIS INTERNET OF THINGS DENGAN METODE LOGIKA FUZZY - Akmal, Muhammad Dhiyadin; Rusli, Moch.; Nurussa’adah, n/a (Jurnal Mahasiswa TEUB, 2024)
The air quality in Indonesia has become a serious concern due to the high levels of pollutants that endanger public health. In 2023, Indonesia ranked 14th as the most polluted country in the world and first in Southeast Asia. PM2.5 and PM10 particulates are the main pollutants having a significant impact. The average concentration of PM2.5 and PM10 in Indonesia reaches 7.4 times the WHO guidelines. The health impacts of these pollutants include irritation, headaches, asthma, heart disease, and lung cancer. With air pollutants posing a threat to public health, continuous monitoring is necessary to identify and measure air pollutant levels. Therefore, this study aims to design and develop an Internet of Things (IoT)-based air quality monitoring system using fuzzy logic in Taman Singha Merjosari, Malang. This system utilizes a PMS5003 sensor to measure PM2.5 and PM10 levels, an ESP32 as a microcontroller, and Blynk Cloud for monitoring. Fuzzy logic is used to process the data and produce air quality outputs. The research results show that the system can operate as designed, with the PMS5003 sensor having an accuracy of 98.69% for PM2.5 and 98.48% for PM10. The fuzzy logic system demonstrates an accuracy of 97.49%. Keywords: Air quality, Taman Singha Merjosari, PM2.5, PM10, fuzzy logic